Application of enzyme preparations for extraction of berry skin phenolics in withered winegrapes. (15th December 2017) - Benucci, I.; Río Segade, S.; Cerreti, M.; Giacosa, S.; Paissoni, M.A.; Liburdi, K.; Bautista-Ortín, A.B.; Gómez-Plaza, E.; Gerbi, V.; Esti, M.; Rolle, L.
Highlights: The impact of exogenous enzymes was studied during maceration of withered grape skins. Single or mixed enzyme activities were tested for phenolic compounds extraction. Skin cell wall composition and mechanical properties affected enzymes effectiveness. Relationships between extractability and mechanical properties were variety dependent. Polygalacturonase favoured skin softening and phenolic extractability in Nebbiolo. Abstract: Postharvest withering of grapes strongly affects the content and extractability of phenolic compounds in the production of sfursat, fortified and passito wines. This work evaluated the effectiveness of enzymes applied individually and/or in multi-enzyme blends, on the extraction of anthocyanins, oligomeric flavanols and polymeric flavanols from withered grape skins during simulated maceration. The study was performed on Vitis vinifera L. cv. Nebbiolo and Barbera because of their different skin phenolic profile and cell wall composition. Our findings highlight that the relationship between skin mechanical properties (berry skin break force and energy) and extraction yield of phenolic compounds is variety dependent. Significant correlations were found between the skin softening associated with cell wall degradation and the extraction of anthocyanins and flavanols in Nebbiolo, for which polygalacturonase, individually or in multi-enzyme blends, plays an important role. In Barbera, the extractability of phenolic compounds was not affected by the presence of exogenous enzymes.